Pengaruh Perkembangan Dunia Digital terhadap Hukum di Indonesia dalam Perlindungan Data Pribadi - Siti Anggita Damayanti S. (Jurnal Hukum Lex Generalis, 2024)
The rapid development of the digital world has had a significant impact on people's lives in the form of positive and negative impacts, one of these developments has an impact in cyberspace as well as legal aspects, especially in the protection of personal data in Indonesia. The increasing use of technology and the internet increases the risk of privacy violations, making strong regulations crucial. The method used is a qualitative approach with in-depth literature study and analysis of related laws and regulations. This research analyzes how digital developments influence legal policies related to Personal Data Protection and evaluates the challenges and effectiveness of regulations in dealing with cyber threats. The research results show the need to strengthen laws and enforce regulations to protect an individual's privacy rights in the digital era.